A Comprehensive View on the Host Factors and Viral Proteins Associated With Porcine Epidemic Diarrhea Virus Infection - Hu, Yi; Xie, Xiaohong; Yang, Lingchen; Wang, Aibing (Frontiers in Microbiology, 2021)
Porcine epidemic diarrhea virus (PEDV), a coronavirus pathogen of the pig intestinal tract, can cause fatal watery diarrhea in piglets, thereby leading huge economic losses to swine industry around the world. The pathogenesis of PEDV has intensively been studied, however, the viral proteins of PEDV and the host factors in target cells, as well as their interactions, which underly the molecular mechanisms of viral infection, remains to be summarized and updated. PEDV has multiple important structural and functional proteins which play various roles in the process of virus infection. Among them, the S and N proteins play vital roles in biological processes related to PEDV survival via interacting with the host cell proteins. Meanwhile, a number of host factors including receptors are required for the infection of PEDV via interacting with the viral proteins, thereby affecting the reproduction and contributing to the life cycle of PEDV. In this review, we provide an update understanding of viral proteins and host factors, as well as their interactions in terms of PEDV infection. Additionally, the effects of cellular factors or events or signaling pathways on PEDV infection are also discussed. Thus, these comprehensive and profound insights should facilitate for the further investigations, the control and prevention of PEDV infection.